Simulation-based Dimensioning of Inventory - Implementing the fundamentals of Lean Management in the production control of a two-stage manufacturing in the automotive industry Simulationsgestützte Auslegung von Lagerbeständen: Umsetzung des Lean-Gedankens in der Produktionssteuerung einer zweistufigen Produktion in der Automobilindustrie - Kohl, Johannes; Risch, Florian; Menzyk, Sabine; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2013)
With increasing application of Lean Manufacturing in the automotive industry, the implementation of a lean production control becomes more and more important. Complex interdependencies have to be taken into consideration, which can hardly be mapped without Simulation. The approach, which is presented in the following elaboration, enables the dimensioning of the stock turnover with only one iteration loop based on a discrete-event Simulation.
CRIS-Team Scopus Importer:2023-03-07